Impact of high-volume, intermediate-volume and low-volume bowel preparation on colonoscopy quality and patient satisfaction: An observational study. Issue 1 (February 2019) - Waldmann, E; Penz, D; Majcher, B; Zagata, J; Šinkovec, H; Heinze, G; Dokladanska, A; Szymanska, A; Trauner, M; Ferlitsch, A; Ferlitsch, M
Background: Although optimal bowel preparation is essential for high-quality screening colonoscopy, documentation of preparation quality, patient satisfaction and adherence is scarce. Aim: The aim of this article is to compare low-volume (LV, 300 ml sodium picosulfate), intermediate-volume (IV, 2 l polyethylene glycol, PEG + ascorbic acid and sodium ascorbate), and high-volume (HV, 4 l PEG) purgatives. Results: A total of 5000 individuals (50.5% women) were enrolled between March 2015 and July 2017 (LV:IV:HV = 3.61:1.54:1). Overall sex- and age-adjusted adenoma detection rate was 25.4% (LV 23.8%, IV 25.4%, HV 29.8%), median age was 59.6 years, and cleansing was successful in 96.8%. Success rates of bowel cleansing were highest with HV (97.6%), followed by LV (97.2%) and IV (95.3%) with OR 2.04 (CI 95% 1.20–3.45, p = 0.008) and OR 1.79 (CI 95% 1.27–2.50, p = 0.001), respectively, compared to IV. A total of 93.5% of the LV group would use the same purgative in the future, 73.2% of IV and 69.4% of HV. A total of 84.4% would prefer overnight preparation, 12.1% same-day preparation. Conclusion: All purgatives investigated showed good bowel cleansing quality results, patient satisfaction and compliance. Improvement in patient information might lead to even higher participation rates in screening colonoscopy since one in five patients stated that bowel preparation worried him or her most prior to colonoscopy.